The Effect of Presto Cooker as an Alternative Sterilizer Device for Standard Dental Equipment - Ariadna Adisattya Djais; Citra Fragrantia Theodorea (Journal of Indonesian Dental Association, 2019)
Introduction: In the suburb area of Indonesia, autoclaves as a sterilizer could not been used optimally due to inadequate electrical capacity. An alternative sterilizer such as a pressure cooker (presto) have been choosen because it has same principle as an autoclave, but it doesn’t required the electrical supply. Nevertheless, the procedure of presto in dentistry remain unclear. Objective: To obtain a standard procedure by using presto for dental instrument. Methods: The effect of presto was observed on aerobic (S. aureus ATCC 25923T), facultative anaerobes (S. mutans ATCC 25175T), anaerobes (P. gingivalis ATCC 33277T) and yeasts (C. albicans ATCC 10231T) which are exposed to the dental mirror. Each dental mirror (triplo) was dipped for 3 minutes on media containing bacteria (106 bacteria/ mL). Furthermore, the dental mirrors were cooked at presto (MAXIM, 7 L, Indonesia) which contained 500 mL of water, for 15, 30 and 45 minutes. Bacterial growth analysis were observed visually and microscopically after Gram staining. Results: In the S. aureus ATCC 25923T and C. albicans ATCC 10231T groups, up to 30 minutes the color of the media showed cloudy but remained clear when sterilized for 45 minutes. Likewise, these groups showed appereance of bacterial growth for 15-30 minutes but didn’t appear to grow in 45 minutes. While in the S. mutans ATCC 25175T and P. gingivalis ATCC 33277T groups, up to 15 minutes the color of the media showed cloudy but remained clear after being sterilized for 30 minutes. In addition, these groups showed appereance of bacterial growth for 15 minutes but absence in 30-45 minutes. Conclusion: Presto can be used as one of alternative equipment to sterilize dental instrument, effectively. The optimal killing time of bacteria and yeast was 45 minutes.